The Association Between Obesity, Chronic Inflammation, Metabolic Disorders and Mood Disorders Among Patients up to 12 Months After Hospitalization for SARS-CoV-2 - Kamila Rachubińska; Alicja Mińko; Iwona Rotter; Joanna Sołek-Pastuszka; Przemysław Ustianowski; Karolina Skonieczna-Żydecka; Elżbieta Grochans (Diagnostics)
Background/Objectives: The relationship between BMI, inflammation, and mental health is complex. A high BMI, especially obesity, is associated with chronic inflammation, which can lead to mental disorders such as depression. Inflammatory cytokines affect neurotransmitters and the stress axis, worsening mental health. Obesity and mental disorders can mutually reinforce each other. New findings show that inflammation can lead to neurobiological changes, and the gut microbiota may play a key role. Obesity has been implicated as a factor in the high mortality and duration of influenza-like illnesses, even in people who do not have other chronic diseases that may increase the risk of complications. The aim of this study was to determine the associations between BMI and chronic inflammation, metabolic disorders, depression, and anxiety in patients hospitalized with COVID-19 up to 12 months after hospitalization. Methods: The study included 248 participants previously hospitalized for SARS-CoV-2 infection up to 12 months after hospitalization. The study was conducted in a multistage design using a diagnostic survey, anthropometric measurements, and laboratory methods. Results: A statistically significantly higher BDI-II score was observed among women. Statistical analysis showed a statistically significant higher GAD-7 score among women and those over 75 years of age. Conclusions: Higher BMI among subjects is often associated with elevated values of inflammatory markers and immune cells, such as WBC, neutrophils, monocytes, and CRP, as well as higher blood glucose levels. These associations may be related to the chronic inflammation and metabolic disorders that often accompany obesity. Lymphocytes and eosinophils may show more varied relationships depending on individual factors and specific health conditions. It is therefore important to continue research in this area.